An orchid bee of the genus Eulaema in Early Miocene Mexican amber (Hymenoptera: Apidae) - Engel, Michael S. (Novitates Paleoentomologicae, 2014)
The first fossil orchid bee from Early Miocene Mexican amber is described and figured.  Eulaema (Apeulaema) zigrasi Engel, new species, represents the first non-meliponine bee fossil documented from Mexican amber as well as the first fossil of its genus.  The new species is distinguished from its congeners and comments are briefly made regarding the geological history of Euglossini.